Noisette: barulho é poder – design e mulheres no punk e no rock - Lemos, Giulia Calloni (My University, 2025)
This work presents a design project based on Human-Centered Design (HCD) aimed at fostering the participation and visibility of women in the punk and rock music genres. The research adopts an intersectional analysis of the music industry and proposes practical solutions to address the specific needs of women in this context. To achieve this, the project utilized interviews and surveys to identify challenges such as infrastructure, musical instrument ergonomics, gender biases, and self-esteem. Applying methodologies from Ellen Lupton, Bernd Löbach, and Stickdorn & Schneider resulted in a solution comprising an ergonomic guitar amplifier connected to a music recording and distribution service exclusively for women, alongside the development of a strong visual identity. This work underscores the role of design as a driver of social transformation, highlighting its capacity to dismantle gender stereotypes and promote women's participation in traditionally exclusive spaces. [resumo fornecido pelo autor]
O presente trabalho contempla um projeto de design com base no Human-Centered Design (HCD) para fomentar a atuação e visibilidade de mulheres nos gêneros musicais punk e rock. A pesquisa parte de uma análise interseccional da indústria musical e propõe soluções práticas que respondam às demandas específicas de mulheres nesse contexto. Para isso, o projeto viabilizou, através de entrevistas e questionário, mapear desafios como infraestrutura, ergonomia dos instrumentos musicais, preconceitos de gênero e autoestima. O uso das metodologias de Ellen Lupton, Bernd Löbach e Stickdorn & Schneider resultou em uma solução que compreende um amplificador de guitarra ergonômico vinculado a um serviço de gravação e distribuição musical exclusivo para mulheres, além da criação de uma identidade visual forte. Este trabalho reforça o papel do design como agente de transformação social, destacando sua capacidade de desconstruir estereótipos de gênero e impulsionar a participação de mulheres em espaços tradicionalmente excludentes. [resumo fornecido pelo autor]
Keywords: Música - Mulheres; Bandas (Música); Grupos de rock; Subcultura; Design